ANALISIS KEBUTUHAN DAN HARAPAN MASYARAKAT KABUPATEN GORONTALO TERHADAP LAYANAN BUS BERBASIS IOT - Hidayat, Andi Sahrul; Bumulo, Nasir; Van Gobel, Ilham Akbar (Universitas Bina Taruna Gorontalo, 2023)
This study aims to analyze people's needs and expectations for IoT-based bus services in Gorontalo District. The research approach involves literature studies, online surveys, direct interviews, and descriptive and qualitative data analysis. The research results show that 43% of Gorontalo Regency residents are interested in switching to using IoT-based bus services, with the majority interested in traveling in the context of work. The development of IoT-based smart buses is expected to improve the quality of transportation, reduce congestion, and accidents, and improve the overall quality of life for society. However, it is recommended that there be collaboration between the government, community, and the private sector to successfully implement this service, especially in Gorontalo Regency.